The Role of Iron in Pediatric Restless Legs Syndrome and Periodic Limb Movements in Sleep - Munzer, Tiffany; Felt, Barbara (Seminars in Neurology, 2017)
Restless legs syndrome (RLS) is a common and treatable neurologic condition in pediatric patients, with a prevalence as high as 2 to 3%. The diagnosis of RLS is made clinically based on an urge to move the legs accompanied by lower extremity discomfort that occurs during rest usually later in the day and is relieved by movement. Periodic limb movements in sleep (PLMS) can overlap with RLS, although PLMS also exists as a separate entity characterized by stereotyped movements of lower extremities in sleep. Both conditions may be highly debilitating and interfere with daily function notably in the areas of educational attainment and behavioral regulation. Iron deficiency has been implicated in the pathophysiology of both RLS and PLMS. Current evidence suggests that treatment of ferritin levels < 50 µg/L may be beneficial in improving pediatric RLS symptoms and comorbid conditions or daytime dysfunction associated with RLS. Areas for future research include (1) clarifying the ferritin or other iron status measure level which predicts iron treatment will provide symptom improvement in pediatric patients, and (2) randomized clinical trials using iron therapy to determine the degree and duration of treatment.
Keywords: restless legs syndrome; periodic limb movements in sleep; iron deficiency; children